Pro Windows Server AppFabric - Kaufman, Stephen; Garber, Danny; SpringerLink (Online service) (Berkeley, CA : Apress, 2010)
This book will teach you all about Windows Server AppFabric (code-named (3z(BDublin(3y(B), a set of extensions to Windows Server that allow it to function as a lightweight, application server. The combination of Windows Server and AppFabric provides an easy-to-manage platform for developing, deploying, and reliably hosting middle-tier WCF/WF services. Windows Server AppFabric fills an important vacuum left in the wake of COM and COM+$1 (Bs demise as the .NET platform has risen to prominence. Provided as an extension to Internet Information Services (IIS), the built-in application server frees you from having to create your own Windows services to perform application hosting. Instead, you can take advantage of plumbing and infrastructure that Microsoft provides for you, freeing you to focus on just your business logic while still being able to deploy n-tier solutions on Windows Server. In this way, Windows Server AppFabric solves the problem of developing, deploying, and reliably hosting middle-tier WCF/WF services. If you$1 (Bre an experienced developer, you$1 (Bll want to learn about Windows Server AppFabric fast, without a lot of reading. And that$1 (Bs what this book is all about. It cuts to the chase and shows you the simplicity and elegance that combine to form Windows Server AppFabric, getting you up to speed fast, so that you can take advantage of all the platform has to offer.s
Choosing AppFabric -- Laying the Foundation -- Understanding the Architecture -- Configuring AppFabric -- Developing WCF Applications with AppFabric -- Developing WF Applications -- Hosting in AppFabric -- Deploying AppFabric Applications -- Advanced Concepts -- Monitoring and Tracking -- Implementing High Availability -- Upgrading to AppFabric.
Keywords: Computer science; Computer Science; Programming Techniques